Class B Gene Expression and the Modified ABC Model in Nongrass Monocots - Akira Kanno; Mutsumi Nakada; Yusuke Akita; Masayo Hirai (The Scientific World Journal)
The discovery of the MADS-box genes and the study of model plants such as Arabidopsis thaliana and Antirrhinum majus have greatly improved our understanding of the molecular mechanisms driving the diversity in floral development. The class B genes, which belong to the MADS-box gene family, are important regulators of the development of petals and stamens in flowering plants. Many nongrass monocot flowers have two whorls of petaloid organs, which are called tepals. To explain this floral morphology, the modified ABC model was proposed. This model was exemplified by the tulip, in which expansion and restriction of class B gene expression is linked to the transition of floral morphologies in whorl 1. The expression patterns of class B genes from many monocot species nicely fit this model; however, those from some species, such as asparagus, do not. In this review, we summarize the relationship between class B gene expression and floral morphology in nongrass monocots, such as Liliales (Liliaceae) and Asparagales species, and discuss the applicability of the modified ABC model to monocot flowers.